A Case of Syrian Child with Cerebral Infarction as an Extraintestinal Manifestation of Ulcerative Colitis - Riham Salloum; Nawras Alhalabi; Mohamad Anas Almidani (Case Reports in Gastrointestinal Medicine)
Thromboembolic complications are rare but well-recognized manifestation of ulcerative colitis, especially because of their associated high mortality. We report a case of a Syrian child admitted to Damascus Hospital with a one-day complaint of sudden onset of numbness followed by weakness in the left lower and upper limbs, right mouth angle deviation, and loss of sphincters’ control. Earlier, she was diagnosed with ulcerative colitis and treated with immunosuppressants. CT and MRI scans revealed focal infarction around the M2-M3 segments of the right middle cerebral artery; she was treated with Aspirin. On discharge, she had significant improved neurological examination and was able to walk. Subsequent proctocolectomy was performed. We highlight the importance of thromboembolism in ulcerative colitis as there is paucity in the literature regarding its management and its symptoms may be overlooked especially in high-load central hospitals. We conducted a brief literature search and summarized findings of similar reported cases.